Pengaruh Pengembangan Sumber Daya Manusia, Human Relatin Dan Work Family Conflict Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Total Cipta Persada) - Novitasari, Mega; Nurhajati, Nurhajati; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to determine the influence of human resource development, human relations and work family conflict on employee performance at PT Total Cipta Persada. The method used in this research is quantitative which aims to explain the position of each variable and its influence between one variable and other variables. The data source used is primary data, namely by distributing Likert scale questionnaires to PT employees. Total Cipta Persada. The population in this study were all employees of PT. The total number of Cipta Persada was 62 people and used a saturated sample where the entire population was sampled in the research. The results of this research are that the variables human resource development, human relations and work family conflict simultaneously have a significant effect on employee performance. Partially, the human resource development variable has a significant effect on employee performance. Partially, the human relations variable has no significant effect on employee performance. Partially, the work family conflict variable has no significant effect on employee performance. Keywords : Human Resource Development, Human Relations, Work Family Conflict, and Employee Performance